Fast-fading, an additional mistaken axiom of wireless-network research. (28th February 2008) - Guardiola, Ivan G.; Matis, Timothy I.
The perplexity of designing an effective underlying communication protocol for Mobile Wireless Ad Hoc Networks (MANETs) is quite prevalent. In recent years, many protocols have been designed and evaluated through discrete event simulators. The lack of fidelity in these simulations, however, often yields results that support the incremental addition of control overhead to increase end-to-end performance measures of the protocol. It is argued herein that this additional overhead is largely ineffective when a fast-fading model is incorporated into the simulation. In particular, a comparison of the well established Ad Hoc On-Demand Distance Vector (AODV) protocol and its simplified version, known as the (AODVjr) protocol, under Ricean and Rayleigh fading models is presented. It is shown that the end-to-end performance of AODV is negligible in comparison to the AODVjr protocol, which possess minimal control overhead, when fast-fading models are incorporated into the simulation environment.